The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1603/0022-0493(2008)101[1331:wdoott]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Within-Plant Distribution of Onion Thrips (Thysanoptera: Thripidae) in Onions

Abstract: Two aspects of the within-plant distribution of Thrips tabaci Lindeman (Thysanoptera: Thripidae) on onion, Allium cepa L., plants were investigated: 1) diurnal variations in the distribution of adults and larvae between basal and upper sections of onion leaves, and 2) between-leaf and within-leaf distribution of the eggs. The diurnal investigations showed that higher proportions of larvae than of adults congregated at the basal sections of plants, particularly when plants were young and thrips density was low.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…Both plant beating and plant dissection showed a strong relationship with visual inspection, so the regression equations can be used in practice to adjust the number of thrips per plant recorded with the two proposed methods. This is particularly useful in estimating the real number of larvae by beating plants because, with this method, larvae are only partly captured, most of them remaining among the leaves at the base of the plant 37. Nonetheless, plant beating is the most suitable sampling method for preserving commercial crops and a more feasible routine practice for growers than counting insects leaf by leaf, directly in the field or after plant dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Both plant beating and plant dissection showed a strong relationship with visual inspection, so the regression equations can be used in practice to adjust the number of thrips per plant recorded with the two proposed methods. This is particularly useful in estimating the real number of larvae by beating plants because, with this method, larvae are only partly captured, most of them remaining among the leaves at the base of the plant 37. Nonetheless, plant beating is the most suitable sampling method for preserving commercial crops and a more feasible routine practice for growers than counting insects leaf by leaf, directly in the field or after plant dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics might involve thickness and rigidity of the cellular walls, the amount of epicuticular waxes, and the wider central angle between the leaves. Th ese features increase the diffi culty of attack by onion thrips on onion plants (Martin and Workman 2006;Mo et al 2008;Morsello et al 2008;Diaz-Montano et al 2010;Silva et al 2015). Chemical substances and the nutritional composition of onion plants infl uence the feeding rate, the development and reproduction of T. tabaci, resulting in plant resistance by antibiosis and antixenosis (Riefl er and Koschier 2009).…”
Section: Fertility Life Table (Flt) Parametersmentioning
confidence: 99%
“…Alfa São Francisco and Sirius showed a significantly smaller angle between the central leaves than Alfa São Francisco RT (Table 2). Cultivars with a wider central angle and more round leaves in horizontal cuts suffer fewer infestations by T. tabaci due to the non-preference of the insects for these leaves due to the smaller contact surface of the leaves with one another compared to more flattened leaves (FREI et al, 2003;MARTIN;WORKMAN, 2006;MO et al, 2008;MORSELLO et al, 2008). Loges et al (2004) observed a relationship between the plant height and thrips density because taller pants have heavier leaves and therefore a wider angle between the central leaves.…”
Section: Comparative Analysis Of Plant Architecturementioning
confidence: 99%
“…tabaci is controlled mainly by means of chemical products, but their efficiency in the control of thrips is low, and high amounts of insecticides are required because the insects have a high escape capacity, high reproductive rate, fast development rate and low sensitivity to the insecticides (BACCI et al, 2008;MO et al, 2008). Some populations of T. tabaci have acquired resistance to the insecticides used in several regions of the world due to the Acta Scientiarum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation